2008
DOI: 10.1152/japplphysiol.90317.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent hypoxia conditioning prevents behavioral deficit and brain oxidative stress in ethanol-withdrawn rats

Abstract: Jung ME, Simpkins JW, Wilson AM, Downey HF, Mallet RT. Intermittent hypoxia conditioning prevents behavioral deficit and brain oxidative stress in ethanol-withdrawn rats. J Appl Physiol 105: 510-517, 2008. First published May 22, 2008 doi:10.1152/japplphysiol.90317.2008.-Intermittent hypoxia (IH) has been found to protect brain from ischemic injury. We investigated whether IH mitigates brain oxidative stress and behavioral deficits in rats subjected to ethanol intoxication and abrupt ethanol withdrawal (EW). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Our findings demonstrating that ethanol withdrawal causes a significant increase in blood pressure are in accordance with previous observations in humans (Ceccanti et al, 2006;Clark & Friedman, 1985;King, Bernardy, Parsons, & Lovallo, 1996). Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings demonstrating that ethanol withdrawal causes a significant increase in blood pressure are in accordance with previous observations in humans (Ceccanti et al, 2006;Clark & Friedman, 1985;King, Bernardy, Parsons, & Lovallo, 1996). Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies suggested that the elevation in blood pressure observed during ethanol withdrawal is transitory (Ceccanti et al, 2006;Clark & Friedman, 1985). However, there is evidence that ethanol withdrawal induces a persistent alteration of blood pressure regulation even when resting pressures are normal, further suggesting that ethanol withdrawal may predict future cardiovascular abnormalities (King et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that biphasic, temporal change in DG proliferation may account for the partial recovery of clinical function in the later stages of IH exposure[31]. In accord, several other preclinical studies demonstrated protective nature of moderate IH suggesting that ischemic preconditioning-like processes may occur[4,32]. For example, in one rodent model, the IH intervention after the ischemic event lead to increased expression of brain derived neurotrophic factor (BDNF), increased hippocampal neurogenesis and functional synaptogenesis, as well as in improvement in spatial learning and long-term memory impairment[24,25].…”
Section: Introductionmentioning
confidence: 96%